Benchmarking deterministic optimization algorithms using an outranking approach. (1st November 2016) - Costa, Lino; Espírito Santo, Isabel; Oliveira, Pedro
Abstract : The comparison of optimization algorithms, through different performance measures, is not straightforward and can be perceived as a multi-criteria problem. Performance profiles, although widely used, has some difficulties in comparing deterministic algorithms. In this work, an outranking approach is studied on a set of examples. The outranking relations, based on concordance and discordance matrices for given threshold values, can be translated into a graph that explicits these relations. The results indicate that the proposed approach elucidates the merits and the disadvantages of different solvers.